Wzmacnianie efektywnej konwersacji na linii uczeń – uczeń. Problemy – rozwiązania – modele - Cybulska-Wal, Alina (Dydaktyka Polonistyczna, 2018)
The overall purpose of this article is help teachers prepare students to have in-depth conversations about content area concepts and topics. Alina Cybulska-Wal claims that interaction is fundamental to learning and identity. In authentic interaction work, students use the facts, grammar, and vocabulary in connected sentences to clarify, fortify, and negotiate complex ideas. In this article author shares ways to model and scaffold classroom conversations. Furthermore, she shows how to manage the most frequent issues.